Care of acute conditions and chronic diseases in Canada and the United States: Rapid systematic review and meta-analysis - Keren M. Escobar; Dorian Murariu; Sharon Munro; Kevin M. Gorey (Journal of Public Health Research, 2019)
This study tested the hypothesis that socioeconomically vulnerable Canadians with diverse acute conditions or chronic diseases have health care access and survival advantages over their counterparts in the USA. A rapid systematic review retrieved 25 studies (34 independent cohorts) published between 2003 and 2018. They were synthesized with a streamlined meta-analysis. Very low-income Canadian patients were consistently and highly advantaged in terms of health care access and survival compared with their counterparts in the USA who lived in poverty and/or were uninsured or underinsured. In aggregate and controlling for specific conditions or diseases and typically 4 to 9 comorbid factors or biomarkers, Canadians’ chances of receiving better health care were estimated to be 36% greater than their American counterparts (RR=1.36, 95% CI 1.35-1.37). This estimate was significantly larger than that based on general patient or non-vulnerable population comparisons (RR=1.09, 95% CI 1.08-1.10). Contrary to prevalent political rhetoric, three studies observed that Americans experience more than twice the risk of long waits for breast or colon cancer care or of dying while they wait for an organ transplant (RR=2.36, 95% CI 2.09-2.66). These findings were replicated across externally valid national studies and more internally valid, metropolitan or provincial/state comparisons. Socioeconomically vulnerable Canadians are consistently and highly advantaged on health care access and outcomes compared to their American counterparts. Less vulnerable comparisons found more modest Canadian advantages. The Affordable Care Act ought to be fully supported including the expansion of Medicaid across all states. Canada’s single payer system ought to be maintained and strengthened, but not through privatization.